Prognostic value of preoperative anti‐thyroglobulin antibody in differentiated thyroid cancer - Jo, Kwanhoon; Kim, Min‐Hee; Ha, Jeonghoon; Lim, Yejee; Lee, Sohee; Bae, Ja Seong; Jung, Chan Kwon; Kang, Moo Il; Cha, Bong Yun; Lim, Dong‐Jun (Clinical endocrinology (Oxford), 2017)
Summary Context The coexistence of differentiated thyroid cancer (DTC) and thyroid autoimmune disease could represent a better or worse prognosis. This study investigated the prognostic importance of preoperative anti‐thyroglobulin antibody (TgAb) in DTC patients. Design and patients This retrospective hospital‐cohort study enrolled 1171 consecutive DTC patients with preoperative TgAb data, who underwent total thyroidectomy between January 2006 and December 2011. Clinical parameters studied included demographics, primary tumour characteristics, radioiodine therapy, thyroid function tests, preoperative thyroglobulin (Tg) and TgAb levels, and cancer persistence/recurrence. Results A total of 254 (21.7%) patients were preoperatively TgAb positive. The percentage positive for thyroid peroxidase (TPO) antibody and lymphocytic thyroiditis was significantly higher in the TgAb‐positive group. The TgAb‐positive group had a significantly higher rate of lymphatic invasion and lymph node metastasis both overall and in patients without TPOAb and lymphocytic thyroiditis (non‐HT group). The mean number of total and central lymph nodes dissected and rate of lateral lymph node dissection were significantly higher in the TgAb‐positive group, both overall and in non‐HT patients. In regression analysis, preoperative TgAb was an independent risk factor for lateral lymph node metastasis. Over 50.2±14.5 months of follow‐up, disease persistence/recurrence was not significantly different between patients with and without TgAb, both overall and in non‐HT patients. Preoperative TgAb showed no significant correlation with final disease status. Conclusion Positive preoperative serum TgAb is associated with worse primary tumour characteristics but rarely showed poor prognosis, probably due to more aggressive treatment of these subjects.